Social geography of the public spaces: social environment vs peripherality - Provotar, Natalia I.; Mezentsev, Kostyantyn V.; Palchuk, Maria V. (Journal of the Belarusian State University. Geography and Geology, 2019)
Transformations of public spaces in different parts of the city have their own characteristics. The fate of public space in the center and on the periphery may seem to be a predetermined by location. But the changing social environment makes its own adjustments. This paper analyzes the influence of the social environment on the public spaces changing in the peripheral part of Kyiv. Research subject is the contemporary transformation of two green public spaces in Kyiv neighborhoods. The aim of the paper is to determine the peculiarities of green public spaces transformations in the peripheral part of Kyiv influenced by the social environment, to determine the nature of its impact on public spaces changes. Analysis of the transformation of public spaces in the peripheral part of Kyiv confirmed the decisive role of the social environment, which is manifesting through the needs of local residents, and made it possible to identify the main factors of change: local initiatives, web forums, cooperation with business, new construction, changes in the residents’ age and social structure, housing ownership. Based on the analysis of users’ perception of public spaces, their accessibility, use, image and integration it was determined the most problematic aspects of the functioning of Kyiv neighborhoods’ public spaces that require priority changes. All this determines the scientific novelty and relevance of the study of green public spaces on the periphery of the city in the context of the social environment of their evolution.
Keywords: city; public space; social environment; peripherality; evolution; transformation; Kyiv